Expanding teaching possibilities frontier by understanding your underachieving learners - How, Pei Lin * (Sunway College Kuala Lumpur, 2015)
This paper studies one of the nine types of academic underachievers that is, the struggling learners that are undertaking Australian-based Pre-University programmes. Primary qualitative data are gathered via interviews, aiming to explore learners’ self-perception, self-discipline and motivation levels to better know the common characteristics and how passive thoughts are formed along their learning journey. This initiative contributes to broadening teachers’ understanding about the presence of academic underachieving learners in classrooms and hence, adding clarity to teachers’ role in providing necessary attention as well as technical assistance to them.